Statement by the Managing Director on the Work Program of the Executive Board. (Policy Papers; Policy Paper ;, 2018)
This Work Program (WP) translates the strategic directions and policy priorities laid out in the Spring 2018 Global Policy Agenda (GPA) Update and the International Monetary and Financial Committee (IMFC) Communique into an Executive Board agenda for the next twelve months.